Effect of Flaring Angle of Transition Structure On the Scouring of outlet structure - Muhammed, Sawsan H.; Hadi, Karem Khalaf (Al-Khwarizmi Engineering Journal, 2019)
The transition structure is considered as the most important hydraulic structure controlling the w/s transtion, morever it decrease the scouring of outlet structure.seven experiment samples for transition structure was used in this research at different angles ( 10° - 90° ).       It was shown that froud number has a clear effect on the depth of the scouring, morever the high discharge rates cause an increase of the ratio between the length of the scour and its depth.       In order to select the best flaring angle it was shown that the angle of 40° has the most discharge rate, least structure length and least angle scour depth, with the firmly of the other factors affecting the scouring of outlet structure.